An Interview with Professor Dieter Birnbacher: Reflections on Ethical Universality - Hanna Schudy; Dieter Birnbacher (Intergenerational Justice Review)
Dieter Birnbacher is professor of philosophy at the University of Düsseldorf and a member of the Foundation for the Rights of Future Generations’ scientific board. In 1988 he published the book Verantwortung für zukünftige Generationen (responsibilities for future generations), which was translated into French (Paris: Presses Universitaires de France 1994) and Polish (Warsaw: Oficyna Naukowa 1999). Hanna Schudy is an ethicist and environmentalist interested in questions of intergenerational responsibility concerning the natural environment. She is a doctoral student at the University of Wroclaw and a DAAD scholarship holder. The interview was conducted in December 2011 at the Heinrich Heine Universität, Duesseldorf. It is part of Ms. Schudy’s current research into “The principle of responsibility in Hans Jonas’ and Dieter Birnbacher’s environmental ethics”.